2021
DOI: 10.1021/acssuschemeng.1c02179
|View full text |Cite
|
Sign up to set email alerts
|

Self-Organized Colloids Thermodynamically Weaken the Effect of Salt on Methane Hydrate Formation

Abstract: Natural gas hydrate deposits are typically rich in organic matter; they together with the host sediments play a crucial role in the nucleation and accumulation of gas hydrates, yet their potential thermodynamic effect on hydrate formation is rarely studied. In the present work, it was found that the deprotonated organic compounds could self-organize with the cations in the solution, forming organic colloids via coordination bonds. Elemental mapping showed that these organic colloids were filled with Ca 2+ and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…As is known, clathrate hydrate is a kind of nonstoichiometric crystalline structure consisting of water and small molecules, where the small guest molecules are physically stored in the polyhedral cages formed by the hydrogen-bonded water molecules under low temperatures and high pressures. ,, To date, it is identified that there are a variety of organic molecules that are molecularly sized and appropriate for being guests in the polyhedral cages of clathrate hydrates, varying from small molecules like H 2 , N 2 , CH 4 , CO 2 , C 2 H 6 , C 2 H 8 , and C 4 H 10 to heavier compounds such as cyclopentane and cyclobutanone. ,, Among these molecules, methane is the most common guest molecular species in nature; ,,, thereby, its corresponding clathrate hydrates are named natural gas hydrates (NGHs) that widely exist in the submarine continental margin and permafrost area. ,,,,, As a result, many studies on the mechanical stability of methane hydrates have been reported. , For example, Cao et al reported via classic molecular dynamics (MD) simulations that factors such as strain rate, temperature, and occupancy of guest molecules in 5 12 6 2 cages have a great effect on the mechanical properties and failure strain of monocrystalline structural I (sI) methane hydrate. In contrast, the crystal orientation has a negligible influence on the tensile response of monocrystalline methane hydrate, for example, along the [110] and [100] directions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As is known, clathrate hydrate is a kind of nonstoichiometric crystalline structure consisting of water and small molecules, where the small guest molecules are physically stored in the polyhedral cages formed by the hydrogen-bonded water molecules under low temperatures and high pressures. ,, To date, it is identified that there are a variety of organic molecules that are molecularly sized and appropriate for being guests in the polyhedral cages of clathrate hydrates, varying from small molecules like H 2 , N 2 , CH 4 , CO 2 , C 2 H 6 , C 2 H 8 , and C 4 H 10 to heavier compounds such as cyclopentane and cyclobutanone. ,, Among these molecules, methane is the most common guest molecular species in nature; ,,, thereby, its corresponding clathrate hydrates are named natural gas hydrates (NGHs) that widely exist in the submarine continental margin and permafrost area. ,,,,, As a result, many studies on the mechanical stability of methane hydrates have been reported. , For example, Cao et al reported via classic molecular dynamics (MD) simulations that factors such as strain rate, temperature, and occupancy of guest molecules in 5 12 6 2 cages have a great effect on the mechanical properties and failure strain of monocrystalline structural I (sI) methane hydrate. In contrast, the crystal orientation has a negligible influence on the tensile response of monocrystalline methane hydrate, for example, along the [110] and [100] directions.…”
Section: Introductionmentioning
confidence: 99%
“…11,15,17−28 To date, it is identified that there are a variety of organic molecules that are molecularly sized and appropriate for being guests in the polyhedral cages of clathrate hydrates, varying from small molecules like H 2 , N 2 , CH 4 , CO 2 , C 2 H 6 , C 2 H 8 , and C 4 H 10 to heavier compounds such as cyclopentane and cyclobutanone. 17,22,25 Among these molecules, methane is the most common guest molecular species in nature; 18,22,29,30 thereby, its corresponding clathrate hydrates are named natural gas hydrates (NGHs) that widely exist in the submarine continental margin and permafrost area. 10,12,18,22,29,30 As a result, many studies on the mechanical stability of methane hydrates have been reported.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Researchers observed that sediments with strong water affinity require higher water saturation for hydrate formation than sediments with low water affinity. , The salinity of sedimentary water also inhibits the hydrate-formation process. Moreover, there is a strong electrostatic interaction between dissolved cations and anions in aqueous solutions containing salt . During hydrate formation, guest molecules will compete with salt ions for molecules of water, and fewer water molecules will be available to construct water cages through hydrogen bonding. , The salinity also increases in the surrounding region of the hydrate when the hydrate molecules are formed.…”
Section: Effect Of Salinity and Porous Media On Co2 Hydrate Formationmentioning
confidence: 99%
“…Over the years, a series of methods for gas production have been developed, such as the depressurization, heat injection, chemical inhibitor, huff and puff, and CO 2 replacement. Carbon dioxide was promoted by the clays in the seabed; methane gas is produced while carbon dioxide is sequestered. However, these methods have certain limitations. The working principle of the depressurization method is to promote the decomposition of the hydrate by reducing the environmental pressure around the hydrate.…”
Section: Reactors For Fundamental Studies On Gas Hydratementioning
confidence: 99%